Testing the Modigliani-Miller theorem directly in the lab: A general equilibrium approach - Jianying Qiu; Prashanth Mahagaonkar (University of Wuppertal, Schumpeter School of Business and Economics, 2009)
In this paper, we directly test the Modigliani-Miller theorem in the lab. Applying a general equilibrium approach and not allowing for arbitrage among firms with different capital structures, we are able to address this issue without making any assumptions about individuals' risk attitudes and initial wealth positions. We find that, consistent with the Modigliani-Miller theorem, experimental subjects well recognized the increased systematic risk of equity with increasing leverage and accordingly demanded higher rate of return. Furthermore, the correlation between the value of the debt and equity is −0.94, which is surprisingly comparable with the −1 predicted by the Modigliani-Miller theorem. Yet, a U shape cost of capital seems to organize the data better.
urn:nbn:de:hbz:468-20090677
Keywords: G32; C91; G12; D53; 330; The Modigliani-Miller Theorem; Experimental Study; Decision Making under Uncertainty; General Equilibrium; Kapitalstruktur; Entscheidung bei Unsicherheit; Allgemeines Gleichgewicht; Test; Kapitalkosten; Theorie